FORMING THE PROFESSIONAL COMPETENCE OF THE FUTURE ENGLISH LANGUAGE TEACHERS OF PRIMARY SCHOOL USING ICT - Liudmyla H. Havrilova (Інформаційні технології і засоби навчання, 2017)
The paper is devoted to the results of experimental implementing ICT into forming the professional competence of future English teachers of primary school. Among the ways of using the electronic educational means offered by the authors there are: developing and using the educational and methodological simulator «Introduction to Interactive Communication» as a local electronic resource on English; implementing the distance learning courses «Practical English Grammar», «Linguistic Country Study» in future specialists’ professional training; work in the electronic services, mastering the programs of infographics during studying the discipline «Methodology of Teaching English». The analysis of the study results showed developing of students’ acmeological linguomethodological aspirations, increasing the motivation for learning, in particular the use of ICT tools in English classes, and proved the effectiveness of the chosen ways of forming the professional competence of future English teachers of primary school.